Congenital Abnormalities of the Breast. A Case Report - Elvira María Martínez Barreto; Miriela Hernández Alba; Mercedes García Calderón (Medisur)
Normal breasts have a wide range of shapes and sizes varying according to cultural, racial, or other conditions, but it is clear that there are abnormalities related to the shape, size, number, location, and so on. Management of these defects requires prior clinical and imaging assessment in addition to plastic surgery. The case of a 14-year-old mestizo girl of rural origin treated at the Paquito González Cueto University Pediatric Hospital due to multiple breast abnormalities and significant asymmetry is presented. Reconstructive surgery of both breasts was performed, placing a breast implant in one of them. The asymmetry and the rest of the malformations were corrected to the patient and her family’s satisfaction. This is the first case of breast implants in the province, hence the interest in presenting it.